Phytochemical, Proximate and Mineral Composition, Antioxidant and Antidiabetic Properties Evaluation and Comparison of Mistletoe Leaves from Moringa and Kolanut Trees - Olugbenga David Oloruntola; Simeon Olugbenga Ayodele (Turkish Journal of Agriculture: Food Science and Technology)
This study evaluates the chemical properties of mistletoe leaves powder from moringa trees (MLPM) and mistletoe leaves powder from kola nut trees (MLPK). The MLPM and MLPK were subjected to phytochemical analysis, vitamin A determination, lipid peroxidation inhibition activity, 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) analysis, proximate and mineral composition analysis, alpha-amylase inhibitory activity and alpha-glucosidase inhibitory activity. Total phenol, steroids, and tannins concentrations were higher in MLPK than in MLPM; steroids was higher in MLPK than in MLPM; whereas total flavonoids and saponins concentrations, were equivalents. MLPK had greater vitamin A concentrations and DPPH than MLPM. The lipid peroxidation inhibition of MLPM and MLPK did not differ significantly. MLPM had higher moisture, crude fibre, and ash content than MLPK. Furthermore, MLPK had larger fat, crude protein, and nitrogen-free extract contents than MLPM. The MLPM and MLPK have similar Zn (0.9 vs. 1.3 mg/kg), Ca (20.1 vs. 13.1 mg/kg), Mg (66.1 vs. 70.2 mg/kg), and P (185.8 vs. 183.5 mg/kg) contents. The alpha-amylase inhibitory action of MLPM (40.40%) and MLPK (35.07%) were similar. MLPK (44.37%), on the other hand, has a stronger alpha-glucose inhibitory action than MLPM (32.47%). Finally, phenol, steroids, tannins, and steroids varied between MLPM and MLPK, with phenol, steroids, and tannins being greater in MLPK. The MLPM had higher vitamin A concentrations and antioxidant activity than MLPK. The MLPM and MLPK inhibited alpha-amylase and alpha-glucosidase activity.